SHE-PWM cascaded multilevel inverter with adjustable DC voltage levels control for STATCOM applications - Law, Kah Haw; Dahidah, M.; Almurib, H. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2014)
This paper presents a new multilevel selective harmonic elimination pulse-width modulation (MSHE-PWM) technique for transformerless static synchronous compensator (STATCOM) system employing cascaded H-bridge inverter (CHI) configuration. The proposed MSHE-PWM method optimizes both the dc-voltage levels and the switching angles, enabling more harmonics to be eliminated without affecting the structure of the inverter circuit. The method provides constant switching angles and linear pattern of dc-voltage levels over the modulation index range. This in turns eliminates the tedious steps required for manipulating the offline calculated switching angles and therefore, easing the implementation of the MSHE-PWM for dynamic systems. Although the method relies on the availability of the variable dc-voltage levels which can be obtained by various topologies, however, the rapid growth and development in the field of power semiconductor devices led to produce high-efficiency dc-dc converters with a relatively high-voltage capacity and for simplicity, a buck dc-dc converter is considered in this paper. Current and voltage closed loop controllers are implemented for both the STATCOM and the buck converter to meet the reactive power demand at different loading conditions. The technique is further compared with an equivalent conventional carrier-based pulse-width modulation to illustrate its enhanced characteristics. The effectiveness and the theoretical analysis of the proposed approach are verified through both simulation and experimental studies.